Salivary IL-21 and IGA responses to a competitive match in elite basketball players - Moreira, A.; Bacurau, R.; Napimoga, M.; Arruda, A.; Freitas, C.; Drago, G.; Aoki, M. (Biology of Sport, 2013)
Athletes engaged in strenuous training might experience transient immune suppression that could lead to greater incidence of upper respiratory tract infections (URTI). Since interleukin 21 (IL-21) stimulates immunoglobulin A (IgA) secreting cells and a low level of this immunoglobulin is associated with increased incidence of URTI, the aim of the present study was to investigate the effect of a basketball match on salivary cortisol (sC), salivary IL-21 (sIL-21) and salivary IgA (sIgA) levels. Twenty male basketball players participated in an official game in two teams (10 players in each team). The saliva samples were collected before the warm-up and approximately 10-15 min after the end of the match and were analysed by ELISA methods. sC concentration increased significantly after the match while sIL-21 level was reduced (p < 0.05). In opposition to the study`s hypothesis, sIgA level did not change in response to the match. The present findings suggest that a basketball match is sufficiently stressful to elevate sC concentration and attenuates the sIL-21 output without compromising the sIgA level. It is reasonable to speculate that the stability of sIgA acute responses to the match, despite the decrement in sIL-21, indicates that other mechanisms rather than IL-21 stimulating B cell proliferation/differentiation might modulate IgA concentration and secretion rate.